Effect of nicotine chewing gum as an adjunct to general practitioner's advice against smoking. Issue 6407 (10th December 1983) - Russell, M A; Merriman, R; Stapleton, J; Taylor, W
Abstract : This study was designed to see whether the offer and prescription of nicotine chewing gum would enhance the efficacy of general practitioners' advice to stop smoking. A sample of 1938 cigarette smokers who attended the surgeries of 34 general practitioners in six group practices were assigned by week of attendance (in a balanced design) to one of three groups: (a) non-intervention controls, (b) advice plus booklet, and (c) advice plus booklet plus the offer of nicotine gum. Follow up was done after four months and one year. The results show a clear advantage for those offered the nicotine gum (p less than 0.001). After correction for those who refused or failed chemical validation and those who switched from cigarettes to a pipe or cigars, the proportions who were abstinent at four months and still abstinent at one year were 3.9%, 4.1%, and 8.8% in the three groups, respectively. These percentages are based on all cigarette smokers who attended the surgeries including those who did not wish to stop and those in the gum group who did not try the gum (47%). The effect of the offer and prescription of gum was to motivate more smokers to try to stop, to increase the success rate among those who tried, and to reduce the relapse rate of those who stopped. The self selected subgroup of 8% who used more than one box of 105 pieces of gum achieved a success rate of 24%. It would be feasible and effective for general practitioners to include the offer of nicotine gum and brief instructions on its use as part of a minimal intervention routine with all cigarette smokers. A general practitioner who adopts such a routine with similar success could expect to achieve about 35-40 long term ex-smokers a year and so save the lives of about 10 of them. If replicated by all general practitioners throughout the country the yield of ex-smokers would be about one million a year.